Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan pada PT Gudang Garam Tbk - Teguh Erawati; Reni Listyawati; Apria Intan Permata Magang; Jumirna Erno Dupe; Rendikus M.Umbu Toda (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to analyze the financial performance of PT Gudang Garam Tbk for the 2019-2022 period using financial ratio analysis, including liquidity ratios (current ratio and quick ratio), solvency (debt to asset ratio and debt to equity ratio), profitability (ROA and ROE), and activity (inventory turnover and total asset turnover). This study uses a descriptive quantitative approach with secondary data obtained from the company’s financial reports available on the official IDX website. The analysis results show that the financial performance of PT Gudang Garam Tbk experienced a decline in liquidity, profitability, and activity ratios, as reflected in the average ratio value below the industry standard, as well as a sharp decline in net profit during the study period. Meanwhile, the solvency ratio shows a good condition with a controlled level of debt funding. This study recommends strategies to increase liquidity, such as reducing current liabilities and optimizing asset and inventory management, to improve the company’s profitability and operational efficiency.